Application-oriented type synthesis and coupling kinematics analysis of a 1Rx2Tyz parallel stabilized platform for tunnel detection system. (21st May 2019) - Liu, Xiao; Liu, Bo; Duan, Yingjie; Bian, Hui
For collecting image high precisely, the application-oriented type synthesis and kinematics analysis for parallel vehicle-based stabilized platform are systematically carried out. Firstly, taking multi-camera install center and vehicle trajectory offset as research objects, the influence of external perturbation on visual system is analyzed quantitatively by numerical calculation and field testing. On this basis, a new type of 2SPR/RPS parallel mechanism with two-translational and one-rotational degree of freedoms is presented. Secondly, by analyzing the motion characteristic of 2SPR/RPS parallel mechanism, the motion adjoint transformation and input–output mapping for parallel vehicle-based stabilized platform are proposed by screw description of rigid-body movement. In addition, an experimental prototype is developed, and the results between numerical examples and semi-physical simulations are compared in order to prove the validity of theoretical analysis. Finally, based on the concept of influence of external perturbations on tunnel detecting system, an external parameter identify method for coupling pose and object distance of visual system is studied. The results can be extended to development, application, and performance evaluation for parallel vehicle-based stabilized platform in next step.